(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
The Haramachi Fault segment in the northeastern part of Honshu Island, Japan, has mainly sinistral fault movements with minor reverse component within the Futaba Fault Zone in the northeastern Japan arc. The 2011 Mw 9.0 earthquake occurred off the Pacific coast of Tohoku which caused large crustal deformations. Despite being the closest active fault to the epicenter, very limited investigation has been conducted on the Futaba Fault Zone. Previous studies used smaller scale topographic maps and fault activity was estimated only from trenching and borehole investigations in the central part of the Haramachi Fault segment. Thus, geometry, kinematic, and recent tectonic activity of the fault segment is not well identified, especially in northern part. In this study, we use a combination of high-resolution DEMs (2-m and 5-m mesh), several types of topographic anaglyph images (slope, negative and positive openness), and conducted field survey to confirm remote sensing interpretation. Subtle surface expression of deformation associated with active faulting, such as deformed terrace risers, deflected drainages, and small fault scarps can now be identified more clearly. Several new fault strands in the northern part of the segment were found supported by fault outcrops found in the field confirming the recent activity of the fault system. The new estimation of the total length of the Haramachi segment produced from the approach of this study yields 25 km, which is capable of producing Mw 6.5 – 7.0 or Mjma 7.2 earthquakes if ruptures were to occur altogether in the future. Moreover, a shallow borehole survey and radiocarbon dating from the soil organic material has revealed the minimal timing estimation of the most recent faulting in the Haramachi segment to be 3694 ± 24 BP. This research provides a revised understanding of active fault distribution and deformation associated with the Haramachi segment and validates the timing of the most recent faulting event more broadly.